2015
DOI: 10.1021/acs.jpca.5b04737
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Reaction of C2H4 and O2 on a Nanosized Gold Cluster: A Computational Study

Abstract: We have investigated the adsorption and reaction mechanisms of C2H4 and O2 catalyzed by a Au38 nanoparticle based on periodic density-functional theory (DFT) calculations. The configurations of the adsorption of C2H4/Au38, O2/Au38, and O/Au38 as well as the coadsorption of C2H4-O2/Au38 were predicted. The calculation results show that C2H4, O2, and O are preferably bound at top (T), bridge (B), and hexagonal (h) sites with adsorption energies of -0.66, -0.99, and -3.93 eV, respectively. The detailed reaction m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 52 publications
0
19
0
Order By: Relevance
“…Using DFT calculations, we found that O 2 is strongly chemisorbed on the C 59 N (–0.32 ∼ −0.84 eV for CN site and −0.66 ∼ −0.99 eV for CC site depending on the various adsorption sites, see Figure S1 and Table S1 in Supporting Information). Compared to those on Pt(111) (–0.58 ∼ −0.72 eV), Pt(110) (–1.48 eV), Pt(001) (–1.30 eV), Pt clusters (–0.72 eV for Pt 2 and −1.08 eV for Pt 3 ), Au clusters (–0.24 eV for Au 4 , ∼ −0.50 eV for Au 7 and Au 9 , −0.60 eV for Au 29 , −0.99 eV for Au 38 ), Pt‐embedded graphene (–1.34 eV), Cu‐embedded graphene (–2.67 eV), Fe‐embedded graphene (–2.09 eV), Au‐embedded graphene (–1.34 eV), the strong ability of C 59 N fullerene for O 2 adsorption (–0.32 ∼ −0.99 eV) creates its possibility as a high active and metal‐free catalyst for ORR and CO oxidation. Two species of O 2 activation on the C 59 N fullerene can be examined: superoxide and peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…Using DFT calculations, we found that O 2 is strongly chemisorbed on the C 59 N (–0.32 ∼ −0.84 eV for CN site and −0.66 ∼ −0.99 eV for CC site depending on the various adsorption sites, see Figure S1 and Table S1 in Supporting Information). Compared to those on Pt(111) (–0.58 ∼ −0.72 eV), Pt(110) (–1.48 eV), Pt(001) (–1.30 eV), Pt clusters (–0.72 eV for Pt 2 and −1.08 eV for Pt 3 ), Au clusters (–0.24 eV for Au 4 , ∼ −0.50 eV for Au 7 and Au 9 , −0.60 eV for Au 29 , −0.99 eV for Au 38 ), Pt‐embedded graphene (–1.34 eV), Cu‐embedded graphene (–2.67 eV), Fe‐embedded graphene (–2.09 eV), Au‐embedded graphene (–1.34 eV), the strong ability of C 59 N fullerene for O 2 adsorption (–0.32 ∼ −0.99 eV) creates its possibility as a high active and metal‐free catalyst for ORR and CO oxidation. Two species of O 2 activation on the C 59 N fullerene can be examined: superoxide and peroxide.…”
Section: Resultsmentioning
confidence: 99%
“…Günay et al investigated O 2 adsorption on a gold cluster and found that stable O 2 adsorption required the presence of an unpaired electron on the gold cluster. Lee et al , calculated O 2 and O adsorption on Au 38 and found that the most stable sites for O 2 and O adsorption are the bridge and hexagonal sites. These investigations showed that only negatively charged even-numbered gold clusters bind a single O 2 molecule in a superoxo-like configuration , and that negatively charged free gold clusters are catalytically active for the CO-combustion reaction, whereas positively charged clusters are inert for the reaction because oxygen cannot be adsorbed …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, some theoretical studies employing clusters as structural models for gold surfaces have been reported. Au 25 and Au 32 , serving as models for Au(111) and Au(100) surfaces, respectively, were found to adsorb ethylene in a di--bonded configuration [20], whereas Au 38 adsorbs C 2 H 4 in a di-bonded configuration on an fcc(100) surface but in abonded configuration on an fcc(111) surface [21]. Additionally, it was shown that C 2 H 4 prefers to bind to corner Au atoms in Au 79 and Au 140 in a -bonded configuration [22,23].…”
Section: Introductionmentioning
confidence: 99%